Motion Syros: tradipitant effective in the treatment of motion sickness; a multicenter, randomized, double-blind, placebo-controlled study - Polymeropoulos, Vasilios M.; Kiely, Leah; Bushman, Margaret L.; Sutherland, E. Blake; Goldberg, Abigail R.; Pham, Annalise X.; Miller, Cameron R.; Mourad, Raina; Davis, Tanner R.; Pham, Nikolas V.; Morgan, Dane B.; Giles, Abigail K.; et al. (Frontiers in Neurology, 2025)
IntroductionMotion sickness has afflicted travelers since ancient times. Neurokinin-1 (NK1) receptor antagonists have therapeutic potential as treatments for the symptoms of motion sickness due to the widespread expression of NK1 receptors throughout important locations in the emetic pathway in the network of brainstem nuclei and the gut. This study evaluated the efficacy of tradipitant, a novel NK1 receptor antagonist, in preventing motion sickness symptoms in variable sea conditions.MethodsA total of 365 adult participants with a history of motion sickness embarked on boat trips under variable sea conditions. Study participants were distributed across 34 boat trips that took place between November 2021 and April 2023 in coastal waters of the United States. Participants were randomized 1:1:1 and received 170 mg tradipitant (n = 120), 85 mg tradipitant (n = 123) or placebo (n = 122). The symptoms of vomiting and nausea were evaluated with questionnaires every 30 min during the approximately four-hour trips. The primary efficacy endpoint for the study was the percentage of vomiting during vehicle travel. Statistical hypothesis testing was performed at the two-sided alpha level of 0.05 unless specified otherwise. Tests were declared statistically significant if the calculated p-value was ≤ 0.05.ResultsThe incidence of vomiting in both dosing arms of tradipitant was significantly lower than the placebo group across all boat trips (170 mg tradipitant = 18.3%, 85 mg tradipitant = 19.5%, placebo = 44.3%, p < 0.0001 for both dose comparisons against placebo). Tradipitant prevented severe nausea and vomiting as compared to participants taking placebo (tradipitant = 18.03%, placebo = 37.70%, p < 0.0001).DiscussionTradipitant 170 mg and 85 mg have been confirmed to be effective in the prevention of vomiting associated with motion sickness across varied sea conditions.Clinical trial registrationClinicalTrials.gov, identifier NCT04327661.